Chemical synthesis of proteins using peptide hydrazides as thioester surrogates - Zheng, Ji-Shen; Tang, Shan; Qi, Yun-Kun; Wang, Zhi-Peng; Liu, Lei (Nature protocols, 2013)
This protocol provides a detailed procedure for the chemical synthesis of proteins through native chemical ligation of peptide hydrazides. The two crucial stages of this protocol are (i) the solid-phase synthesis of peptide hydrazides via Fmoc chemistry and (ii) the native chemical ligation of peptide hydrazides through in situ NaNO 2 activation and thiolysis. This protocol may be of help in the synthesis of proteins that are not easily produced by recombinant technology and that include acid-sensitive modifications; it also does not involve the use of hazardous HF. The utility of the protocol is shown for the total synthesis of 140-aa-long α-synuclein, a protein that has an important role in the development of Parkinson's disease. The whole synthesis of the target protein α-synuclein in milligram scale takes ∼30 working days.